Evaluation of Different Growing Media for Tomato and Sweet Pepper Seedlings Raising in Pokhara, Nepal - Lohani, Santosh; Adhikari, Saroj; Aryal, Lok Nath; Bhusal, Yubraj; Kadariya, Manahar; Aryal, Sunil (Journal of Agriculture and Environment, 2023)
Nine different compositions of growing media were evaluated for growing tomato and capsicum in two consecutive years (2020 and 2021). Experiments were conducted in Randomized Complete Block Design (RCBD) under rain shelter (poly house) with three replications. The growing media were Cocopeat, FYM+Cocopit+Perlite, FYM+ Cocopit+Vermiculite, FYM+Perlite, FYM+Soil, FYM+Vermiculite, Vermicompost+Perlite, Vermicompost +Soil and Vermicompost+Vermiculite. There were significant (P